2020
DOI: 10.1038/s41598-020-75169-4
|View full text |Cite
|
Sign up to set email alerts
|

Innate local response and tissue recovery following application of high density microarray patches to human skin

Abstract: The development of microarray patches for vaccine application has the potential to revolutionise vaccine delivery. Microarray patches (MAP) reduce risks of needle stick injury, do not require reconstitution and have the potential to enhance immune responses using a fractional vaccine dose. To date, the majority of research has focused on vaccine delivery with little characterisation of local skin response and recovery. Here we study in detail the immediate local skin response and recovery of the skin post high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 37 publications
4
34
1
1
Order By: Relevance
“…In our study, no significant differences in micropore closure time were observed between the upper arm, volar forearm, and abdomen after MN application. This result may be supported by the study of Muller et al [49], which investigated skin recovery in healthy adults after applica-tion of microarray patches to the upper arm and volar forearm by monitoring TEWL post-microarray application. They found no difference in skin recovery rates between the 2 sites, as TEWL response returned to baseline for both sites within 48 h [49].…”
Section: Micropore Formation and Closure Timementioning
confidence: 71%
See 1 more Smart Citation
“…In our study, no significant differences in micropore closure time were observed between the upper arm, volar forearm, and abdomen after MN application. This result may be supported by the study of Muller et al [49], which investigated skin recovery in healthy adults after applica-tion of microarray patches to the upper arm and volar forearm by monitoring TEWL post-microarray application. They found no difference in skin recovery rates between the 2 sites, as TEWL response returned to baseline for both sites within 48 h [49].…”
Section: Micropore Formation and Closure Timementioning
confidence: 71%
“…This result may be supported by the study of Muller et al [49], which investigated skin recovery in healthy adults after applica-tion of microarray patches to the upper arm and volar forearm by monitoring TEWL post-microarray application. They found no difference in skin recovery rates between the 2 sites, as TEWL response returned to baseline for both sites within 48 h [49]. While in our current study no significant differences were observed between the anatomical sites, micropore closure time at the abdomen was overall longer than at the upper arm and volar forearm, and the number of subjects with micropore closure time exceeding 72 h at the abdomen was more than the other 2 anatomical locations.…”
Section: Micropore Formation and Closure Timementioning
confidence: 71%
“…Vaccine is coated onto the microprojections via a nitrogen-jet-based drying process ( 20 ) before application to the skin at a velocity of 18-20 m/s via a spring-loaded applicator. This delivers the vaccine directly to the dermal and upper dermal layers of the skin, which are rich in antigen-presenting cells ( 2123 ). This vaccine modality offers considerable advantages in thermostability and antigenicity ( 20, 24 ) with dose-sparing of a large range of vaccines previously observed ( 2532 ).…”
Section: Main Textmentioning
confidence: 99%
“…Vaccine is coated onto the microprojections via a nitrogen-jet-based drying process (20) before application to the skin at a velocity of 18-20 m/s via a spring-loaded applicator. This delivers the vaccine directly to the dermal and upper dermal layers of the skin, which are rich in antigen-presenting cells (21)(22)(23).…”
Section: Main Textmentioning
confidence: 99%
“…It has been suggested that predispositions direct the chick’s attention toward the kind of stimuli from which the animal would benefit the most 24 26 . In fact, chicks have predisposed (not learned) preferences for patterns of motion 27 29 and arrangments of features 30 32 that are similar to those found in living animals, such as biological motion 33 , 34 , self-propulsion 35 , 36 or even specific colours such as red (which is the colour of the comb, a zone of the head important for individual recognition 37 ). Predispositions for patterns of motions and colours can affect the acquisition of imprinting memory 25 .…”
Section: Introductionmentioning
confidence: 99%